In-Depth Learning for Students with Deafness in Special Schools: A Literature Study - Ila Kamila; Oom Sitti Homdijah; Budi Susetyo; Iding Tarsidi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
The Deep Learning paradigm offers the potential to improve learning quality through conceptual understanding and metacognitive reflection. However, studies of its application in deaf education in Indonesia are very limited. This study aims to conduct a systematic literature review to map the opportunities, challenges, and conceptual models of deep learning relevant to deaf students. This study uses a qualitative literature review with a systematic integrative review design, which is analyzed using thematic content analysis across the stages of open coding, axial coding, and selective coding. The research identified three key opportunities for implementing Deep Learning: optimizing visual and kinesthetic modalities through interactive media, developing self-regulated learning through visual reflection, and strengthening social collaboration through community learning. These findings resulted in recommendations for project-based visual-reflective learning models, interactive media, and portfolio assessments. This research encourages teachers to design learning that stimulates deep thinking; schools to strengthen professional collaboration and provide visual learning environments; and the government to improve teacher training and inclusive technology facilities. Further research is recommended to test the effectiveness of this model through experiments and field implementation in various special needs schools (SLB).